Comparison of Antim icrobial Activity of Honey from Various Floral Sources against Food Spoilage Bacteria - Ghani, Dilara; Siddiqua, Ishrat; Mowlah, Aleya (Bangladesh Journal of Nutrition, 2014)
Honey is a natural product that has found to possess numerous beneficial properties. In this study, antimicrobial activity of honey produced by various floral sources: black cumin, litchi, mustard, wild honey from the forests of Sundarban (one was new and another was stored) and a commercial honey (Dabur honey) was tested against four food spoilage bacteria: Staphylococcus aureus, Escherichia coli, Bacillus cereus and Salmonella spp. by disc diffusion assay. All honeys were checked at four concentrations (1%, 5%, 10% and 100% v/v) and the mean zones of inhibition were measured. The effect of temperature on the antibacterial activity was determined by treating the honey samples at three different temperatures: 50°C, 75°C and 100°C. Some physicochemical properties such as color, pH, moisture content and brix value of these honeys were also measured using standard methods. Research findings showed that, all honey samples had an inhibitory effect on the growth of bacteria. Among them, honey from black cumin flower was found to be the most active followed by mustard, litchi and Sundarban honeys. Of all honeys, commercial honey was the least active. None of the honeys were active at 1% (v/v) concentration, as the concentration increased activity also increased. Although, antibacterial activity found to be reduced with increasing temperature treatment, but it was remain effective even after heat treatment at 100°C for 30 minutes. The results of this study confirmed the possibility of using honey in preventing the growth of food spoilage bacteria to extend the shelf life of foods. Bangladesh J. Nutr. Vol. 26-27, December 2014, P-15-24